2016
DOI: 10.1007/s00192-016-2993-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pelvic floor disorders: international urogynecological association research and development committee opinion

Abstract: Pelvic floor disorders have a long latency, and may go through periods of remission, thus making causality difficult to confirm. Nevertheless, prevention strategies targeting modifiable risk factors should be incorporated into clinical practice before the absence of symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“…Many of the pelvic floor problems that afflict women can be prevented by proper risk assessment, patient education, and early intervention 7 . Until recently, a more passive, sometimes fatalistic attitude has prevailed among women and their care providers.…”
Section: Pre‐reproductive Agesmentioning
confidence: 99%
“…Many of the pelvic floor problems that afflict women can be prevented by proper risk assessment, patient education, and early intervention 7 . Until recently, a more passive, sometimes fatalistic attitude has prevailed among women and their care providers.…”
Section: Pre‐reproductive Agesmentioning
confidence: 99%
“…8 Treatment should include the reduction of risks and previous research has identified multiple risk factors for UI that may be modifiable. 9 These factors include environmental, 10 psychological, 11 and lifestyle and behavioral. 12,13 In addition, significant associations between specific toileting behaviors and presence of lower urinary tract symptoms (LUTS), predominantly UI, were found in employed women, 13 female nurses, 14,15 and young women.…”
Section: Introductionmentioning
confidence: 99%
“…2 Women have a 2 to 8 times higher risk of anterior cruciate ligament (ACL) injuries, 3 2 to 10 times higher risk of patellofemoral pain syndrome, 4-6 a 3 to 12 times higher risk of stress fractures, 6,7 2 times higher risk of symptomatic osteoarthritis after the age of 60, 8 3 to 4 times higher risk of osteoporosis, 9 2 times higher risk of osteoporosisrelated fracture, 9 and 2 to 3 times higher risk of pelvic floor dysfunction and urinary incontinence. [10][11][12] Seventy percent to 86% of women in the United States and Scandinavian countries report lumbar and/or pelvic girdle pain during their pregnancies. 13 Up to 25% of women experience daily chronic pelvic pain (defined as pelvic pain lasting longer than 6 months).…”
Section: Introductionmentioning
confidence: 99%
“…Women live 7 years longer than men (on average) and experience a higher level of chronic illness, including musculoskeletal disorders, in their lifetime . Women have a 2 to 8 times higher risk of anterior cruciate ligament (ACL) injuries, 2 to 10 times higher risk of patellofemoral pain syndrome, a 3 to 12 times higher risk of stress fractures, 2 times higher risk of symptomatic osteoarthritis after the age of 60, 3 to 4 times higher risk of osteoporosis, 2 times higher risk of osteoporosis‐related fracture, and 2 to 3 times higher risk of pelvic floor dysfunction and urinary incontinence . Seventy percent to 86% of women in the United States and Scandinavian countries report lumbar and/or pelvic girdle pain during their pregnancies .…”
Section: Introductionmentioning
confidence: 99%